Enhancing the sports training of elite female athletes in academic rowing - Malikov, M.; Tyshchenko, V.; Hlukhov, I.; Drobot, K.; Dubachinskiy, O.; Zubov, V.; Pasichnyk, V. (Journal of Physical Education and Sport, 2024)
Currently, the central concern in the training of athletes is the pursuit of effective management strategies for the training process. This involves leveraging insights into the structure of competitive activities, incorporating general principles of athletic development, and tailoring training approaches to individual athlete capabilities.